2009
DOI: 10.2183/pjab.85.83
|View full text |Cite
|
Sign up to set email alerts
|

Raman Tensors and their application in structural studies of biological systems

Abstract: The Raman scattering of a molecule is generated by interactions of its electrons with incident light. The electric vector of the Raman scattered light is related to the electric vector of the incident light through a characteristic Raman tensor. A unique Raman tensor exists for each Raman-active molecular vibrational mode. In the case of biologically important macromolecules Raman tensors have been determined for a few hundred vibrational Raman bands. These include proteins and their amino acid constituents, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 53 publications
0
57
0
Order By: Relevance
“…In general, a Raman tensor relates the polarization direction of the exciting light to the polarization direction of the scattered light . A Raman tensor corresponding to a particular vibrational mode can be described in terms of three non‐zero components (principal axes) that can be determined using polarized Raman spectroscopic measurements . The procedure for determining the orientation of chemical groups based on polarized Raman spectroscopy has been previously reported …”
Section: Resultsmentioning
confidence: 83%
“…In general, a Raman tensor relates the polarization direction of the exciting light to the polarization direction of the scattered light . A Raman tensor corresponding to a particular vibrational mode can be described in terms of three non‐zero components (principal axes) that can be determined using polarized Raman spectroscopic measurements . The procedure for determining the orientation of chemical groups based on polarized Raman spectroscopy has been previously reported …”
Section: Resultsmentioning
confidence: 83%
“…We determine the orientations of the local-mode ls based on the transition charges in the amide plane 66,67 and the orientations and magnitudes of the as based on previous work of Tsuboi et al 68 The orientation distribution of the ester groups in the MGDG/PG lipid monolayer layer was determined from a published MD trajectory 69 .…”
Section: Methodsmentioning
confidence: 99%
“…The largest polarizability oscillation for the amide I vibration of the isolated amide chromophore occurs along the line that is in the plane of the peptide group and at an angle of 34°with respect to the peptide CO bond. 79,84 However, Krim et al has shown that vibrations of adjacent amide chromophores are coupled and delocalized along the polypeptide backbone. 51,85 Furthermore, Asher and co-workers have experimentally demonstrated that the amide I vibrational mode exhibited noticeable interamide coupling in the α-helix conformation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…89 As mentioned previously, the angle of 34°has been reported between this tensor and the peptide CO bond for the isolated amide chromophore. 79,84 Once the angle between the carbonyl group and the PART is known, the orientation order parameters for the CO bonds, ⟨P 2 ⟩ CO and ⟨P 4 ⟩ CO , can be calculated from the experimentally determined ⟨P 2 ⟩ and ⟨P 4 ⟩ values using the Legendre addition theorem. 90 Figure 6B shows the most probable orientation distribution function of CO groups in the disordered parts of an insulin fibril ( Figure 6B, red curve) calculated based on ⟨P 2 ⟩ CO and ⟨P 4 ⟩ CO .…”
Section: ■ Results and Discussionmentioning
confidence: 99%